Linguistic Power Moves: A Corpus-Based Study of Authority in Classroom Discourse - Tahreem Fatima; Dr. Naveed Nawaz Ahmad (Corresponding Author); Dr. Rabia Faiz; Dr. Hafiz Ahmad Bilal (`, 2025)
Classroom authority is not a given thing, we actually create it during a conversation. In this paper, the researchers consider daily discussions in the classroom between the teachers and the students to see how we are using language to assert or demand power. Applying discourse analysis and sociolinguistic data, the attention is drawn to the fact that modality, politeness, turn-taking, and speech acts can be mixed in case people negotiate their power. This builds upon previous research in the field of classroom discourse by showing that power is negotiated in an ever present way through talk rather than being imposed upon people by higher authorities. By speaking up, changing the voice or providing more details, we adjust the power dynamics in favour of a more cooperative classroom environment. Awareness of these patterns will enable the teachers to intervene more strategically in order to create a productive learning environment. Sociolinguistics, discourse analysis, power relations, student engagement, and the social, cultural and institutional norms that are involved in forming authority are all contextual and co-constitutive and impactful in this process. Keywords: Classroom authority, modality, teacher-student interaction, politeness